Art education to train teachers in human rights and sexual diversity - Huerta, Ricard (Pulso. Revista de educación, 2020)
This work analyzes the possibilities of an online museum to offer Primary School teachers innovative resources, free and accessible materials, promoting and understanding LGBT realities through art. The use of digital technology, the arts and the humanities, generate pedagogical drifts with actions of a social, political and cultural order, in defense of Human Rights. Art education advances towards porous models, and teachers needs more information. We incorporate these themes into the initial teacher training for Primary School. The methodology used starts from ethnographic personal narratives as life stories, since the author exposes the professional motives led him to the creation of Museari, a virtual museum that defends sexual diversity from the arts and education. The article offers examples of artists, with works that serve to address these issues in the classroom, also stressing the importance of LGTB cinema, very present in Museari.
Keywords: Art; Education; Human rights; Museum; Sexual diversity; Teacher training